PHARMACOLOGICAL CORRECTION OF CERTAIN PHYSIOLOGICAL AND BIOCHEMICAL CHANGES IN EXPERIMENTAL ALCOHOL INTOXICATION IN LABORATORY ANIMALS - Muratbaeva.B.J (International Journal of Literature and Language Studies, 2026)
Abstract: Alcohol intoxication is associated with numerous physiological and biochemical disturbances that adversely affect the functioning of various organs and systems. Experimental studies in laboratory animals provide valuable opportunities to investigate the mechanisms of alcohol-induced toxicity and to evaluate potential therapeutic interventions. Alcohol metabolism leads to the formation of toxic metabolites and reactive oxygen species, which contribute to oxidative stress, cellular damage, and metabolic dysfunction. These alterations are often reflected in changes in hematological and biochemical parameters, including liver enzyme activity, bilirubin levels, and antioxidant status. Pharmacological correction represents a promising approach for reducing the harmful effects of alcohol intoxication through the use of antioxidants, hepatoprotective agents, vitamins, and other biologically active compounds. The investigation of pharmacological interventions in experimental alcohol intoxication may contribute to a better understanding of the underlying pathophysiological processes and support the development of effective strategies for the prevention and treatment of alcohol-related disorders.